Creating a new brand name: a research with the case study method - Huseynli, Bahman (Creativity Studies, 2025)
With the rapid growth of the fast-food restaurant sector in Azerbaijan, the number of domestic and international enterprises is increasing. With this, the brand name becomes very important. Based on this, the purpose of the study is to create brand names for new fast-food restaurants. The study is qualitative research and was analysed by case method. As a result of the study, brand names were suggested by participants, and these brand names were analysed. Suggested brand names were classified before being analysed. Brand names classified in 7 groups as creative, national, fast, delicious, local, global, and competitive were then analysed. Among the brand names suggested by the participants, the most suitable were for the creative concept. Brand names with the meaning national suggested by the participants in both cases are among the most recommended. When evaluated in general, a total of 118 brand names have been suggested, and among these names, more suggested names are suitable for the words national, creative, local, delicious, global, food, and fast. The rapid development of the fast-food sector in Azerbaijan and the interest of both local and global companies in this sector create a need for new brand names. In this respect, it is thought that the article will contribute to the academic literature and practitioners.